One drop can be beneficial, one swig can be deadly: tetrahydrozoline intoxication - Paksu, Muhammet Şükrü; Paksu, Şule; Akkuş, Tuğrul; Baysal, Kemal (The Turkish Journal of Pediatrics, 2012)
Tetrahydrozoline is a commonly used imidazoline derivative with serious side effects and toxicity, particularly in small children. A one-year-old boy was admitted to the emergency department (ED) after he accidentally ingested about half a bottle of nasal decongestant solution containing tetrahydrozoline. He was unconscious, hypothermic and bradycardic on presentation. His respiration was irregular and superficial, and blood pressure was borderline hypotensive. His skin was pale and cold. Atropine was administered twice for symptomatic bradycardia, and the child was transferred to the pediatric intensive care unit (PICU). During the 12th hour of observation, vital signs returned to normal and there was no need for mechanical ventilation. Although suitable room temperature with passive warming was applied, hypothermia continued for approximately 24 hours. The patient was discharged on the second day of admission. There were no complaints one week later, and the physical examination was normal. We report a case of accidental tetrahydrozoline intoxication with life-threatening events accompanying hypothermia in a small infant.